(untitled) (Revista Direito em Debate, 2021)
This article aims to develop reflections about the judicialization process of the social relationships, especially about the Maria da Penha Law, through the qualitative research that leads to understanding its effects progression about gender violence against women. It either pretends to assimilate the origins of the judicialization phenomenon in social revindication and manifestation towards the state neglect, following the fight against impunity request. Therefore, a bibliographic and a documental review were conducted, through the study about the judicialization concept and the analysis of the Maria da Penha Law. The research points out that it is important to question the proliferation of the penalizing primary perspective and to contribute to the gender violence prevention actions.